O zaščiti vida v sodobnem času - Jurekovič, Branimir (Obzornik zdravstvene nege, 1979)
Basic data concerning the classification and causes of blindness in the world are given. Some well known factors causing sight impairement are elucidated from the aspect of recent discoveries in this field. The author presents some agents injurious to sight to which man is exposed daily but have remained obseure so far. A need is emphasized of continuous following and evaluating all noxious factors, which should be imperative for all health workers.